Археологічні розвідки в районі оз. Тобечик - Шевченко, Т.М. (Археологічні дослідження в Україні, 2010)
Materials of visual archaeological prospecting at the area to the north from Lake Tobechyk are published which allow to give a more precise description to settlements Tobechyk 3 and 8, and also to fix the new sites at chora of Nimphaeum.